Limited evidence for trans-generational effects of maternal dietary supplementation with ω-3 fatty acids on immunity in broiler chickens. Issue 2 (February 2015) - Koppenol, Astrid; Delezie, Evelyne; Parmentier, Henk K.; Buyse, Johan; Everaert, Nadia
Highlights Only subtle changes were found in the offspring immune response after maternal supplementation of n-3 fatty acids. Maternal n-3 supplementation did not affect the production of acute phase proteins, with the exception of ovotransferin. Freund's adjuvant was not the best agent to trigger acute phase response nor cytokine production. Maternal n-3 supplementation had no effect on plasma cytokine concentrations Maternal n-3 supplementation had no effect on offspring antibody response.